J. Laurence Laughlin papers - Laughlin, J. Laurence (James Laurence), 1850-1933.; Laughlin, J. Laurence (James Laurence), 1850-1933.
Correspondence, lectures, writings, articles, notes, financial papers, printed matter, clippings, and other papers relating chiefly to Laughlin's career with the University of Chicago Dept. of Political Economy and as editor of the Journal of Political Economy. Also documents his work with groups concerned with banking, credit, money, and related economic matters. Subjects include economics, finance, the silver question, and tariff. Includes a manuscript of Laughlin's work The Federal Reserve Act, Its Origin and Problems (1933). Correspondents include Leon C. Marshall, Paul M. Warburg, and Henry Parker Willis.
Economist, educator, and editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Marshall, Leon C. -- 1879- -- Correspondence; Warburg, Paul M. -- 1868-1932 -- Correspondence; Willis, Henry Parker, -- 1874-1937 -- Correspondence; University of Chicago. -- Department of Political Economy; Journal of political economy; Banks and banking; Credit; Economics; Economics -- Periodicals; Economics -- Study and teaching; Finance; Money; Silver question; Tariff; Authors; Economists; Educators